Solitary Bone Cyst: A Case Report and Review of Literature - Ajay R Bhoosreddy; Rajeev M Gadgil; Seema A Bhoosreddy; Gauri N Velankiwar (Wolters Kluwer Medknow Publications, 2010)
Solitary bone cyst (SEC) is a rare disorder of the jaw bones, as well as other skeletal bones, particularly the long bones. It usually occurs in the metaphyseal region of long bones comprising only around 2% of all bone cysts affecting this area. Solitary bone cyst is an asymptomatic, slow growing, usually nonexpansile lesion commonly diagnosed incidentally during routine radiographic examination of the jaw bones. Its etiology is not clear and trauma has not been definitely determined to be the cause. It occurs mainly in children and young adults, and the body of the mandible is the most common site On the basis of the literature available, opinions concerning the etiology, pathogenesiss and treatment of this disorder have been presented. A case of incidentally diagnosed solitary bone cyst of the mandible in a 22 years old female patient is presented. The clinical, radiographic and histopathologic features of this cyst have been demonstrated.